2021
DOI: 10.3389/fphar.2020.626502
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of the Inflammasome and Pyroptosis in Brain

Abstract: Background: Considering the pivotal role of inflammasome/pyroptosis in biological function, we visually analyzed the research hotspots of inflammasome/pyroptosis related to the brain in this work through the method of bibliometrics from the Web of Science (WOS) Core database over the past two decades.Methods: Documents were retrieved from WOS Core Collection on October 16, 2020. The search terms and strategies used for the WOS database are as follow: # 1, “pyroptosis”; # 2, “pyroptotic”; # 3, “inflammasome”; #… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 114 publications
(162 reference statements)
0
56
0
Order By: Relevance
“…Co-citation analysis indicates the relationship between items based on the frequency they are cited together, with TLS being calculated to assess the total link strength (Zhao et al, 2018 ; Chen et al, 2021 ). The journal co-citation analysis showed that Ultrasound in Medicine and Biology, Journal of Controlled Release , and Journal of the Acoustical Society of America were the top three journals with the largest TLS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Co-citation analysis indicates the relationship between items based on the frequency they are cited together, with TLS being calculated to assess the total link strength (Zhao et al, 2018 ; Chen et al, 2021 ). The journal co-citation analysis showed that Ultrasound in Medicine and Biology, Journal of Controlled Release , and Journal of the Acoustical Society of America were the top three journals with the largest TLS.…”
Section: Discussionmentioning
confidence: 99%
“…This database was chosen for three reasons. First, in contrast to other popular databases such as Google Scholar, PubMed, Scopus, or Embase, WOSCC is the most comprehensive and authoritative one across scientific disciplines (Chen et al, 2020 , 2021 ). Second, it is a typical citation database containing literature abstracts and other relevant data such as citation and research collaboration information, facilitating for scientometric analysis (Yeung et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WoSCC covers a considerable amount of highquality scientific literature in the biomedical, natural, and social sciences, and it was used as the main data source. It is regarded as one of the most widely accepted and suitable databases for bibliometric analysis of scientific publications (Shi et al, 2020;Wang et al, 2019;Merigó et al, 2019;Chen et al, 2021). In addition, the Scopus database (searched at https:// www.scopus.com/) was also searched to validate the results obtained from the WoSCC and provided as supplementary material.…”
Section: Data Sourcementioning
confidence: 99%
“…Second, we employed two widely used scientometric software tools to conduct the present study in paralle, and could get more comprehensive and reliable analysis results. Third, unlike previous similar bibliometric studies, whose results derive from only one database, two databases (WoSCC and Scopus) were employed in this study, which could provide a comprehensive analysis of ultrasound microbubble research (Merigó et al, 2019;Wang et al, 2019;Shi et al, 2020;Chen et al, 2021).…”
Section: Strengths and Limitationsmentioning
confidence: 99%